2010
DOI: 10.1159/000295176
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcome of Conservative Management versus Fetal Intervention for Twin Reversed Arterial Perfusion Sequence with a Small Acardiac Twin

Abstract: Objective: To examine the outcomes of patients with twin reversed arterial perfusion (TRAP) sequence in which the acardiac twin was ≤50% the weight of the pump twin. Methods: This was a retrospective study conducted with institutional review board approval. The records of all patients referred to UCSF for suspected diagnosis of TRAP between 1994 and 2009 were reviewed (n = 76). Patients with pregnancies complicated by TRAP with an acardiac twin ≤50% the weight of the pump twin were included (21 patients). Excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 16 publications
1
45
1
1
Order By: Relevance
“…Our study shows that 8 of the 11 pump twins who were treated with RFA (73%) survived without complications. Although this survival rate is lower in comparison with other studies, which are 92%, 86%, 94%, 100%, respectively [7,[9][10][11], our results are worthwhile as the first and largest series performed in Korea. There are only 2 other case reports in Korea on the successful use of in utero intervention to manage the TRAP sequence.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Our study shows that 8 of the 11 pump twins who were treated with RFA (73%) survived without complications. Although this survival rate is lower in comparison with other studies, which are 92%, 86%, 94%, 100%, respectively [7,[9][10][11], our results are worthwhile as the first and largest series performed in Korea. There are only 2 other case reports in Korea on the successful use of in utero intervention to manage the TRAP sequence.…”
Section: Discussioncontrasting
confidence: 60%
“…The second series by Livingston et al [10] demonstrated that using a 19-gauge needle resulted in only 1 of 13 cases (8%) that were treated with RFA to be delivered in less than 32 weeks due to PPROM. Although no details regarding preterm delivery were noted in the latest series, the authors reported a 100% survival rate for their 7 RFA cases [11]. Along with the development of these instruments, RFA has become known as a safe and effective treatment modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The conservative approach can be considered if the acardiac fetus is small, its growth is rather slower and the pump fetus has no complications. 8,9 Yet expectant management can yield to perinatal mortality due to the development of heart failure or preterm delivery as shown in a case series of Pagani et al 10 It's controversial whether conservative management or therapeutic treatment is better in TRAP-sequence. It seems appropriate to choose an interventional approach in the cases of hydrops, polyhidroamnios and abnormal vascular anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques partly target the umbilical cord vessels using coil occlusion ligation, laser coagulation or bipolar coagulation. Other methods are aimed at the intrafetal umbilical vessels using alcohol injection, thermocoagulation, laser coagulation, radiofrequency or, very recently, high-intensity focused ultrasound (22). Laser coagulation of the vascular anastomoses on the placental surface has been proven as an effective and safe measure in many studies and case reports (23).…”
Section: Discussionmentioning
confidence: 99%